Sociolinguistics Study of Slang Words Used in Movie â€œSpiderman Homecomingâ€ - Aqib Pranata; Nasrullah Nasrullah (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2023)
Sociolinguistics is a branch of linguistics concerned with the study of socially related languages. One of the language variations is slang.Â  Slang is a variety that used by young people or persons from the same social group, and it consists of free-style construction words with particular qualities. Previous research examined the use of slang in movies and its relationship to sociolinguistics. However, previous research results lack in the showing support that strengthens the discussion by expert opinion. The movie Spider-man: Homecoming was chosen as the object in this research. Descriptive-qualitative was used as its research method. While documentation study was used to obtain data in this study.Â  This research investigated classifications and the reasons why the characters in the movie use slang words. The findings of this study show five classifications of slang from Allan & Burridge's theory. In this movie, four of the five slang classifications from Allan & Burridge's theory: fresh and creative, flippant, imitative, and clipping, were found. Fresh & creative is more commonly found in this movie because this type is used for swearing and even to show anger. Besides, there are reasons why slang words are usually used such as, to address, to show an impression, to show intimacy, to reveal anger, and to humiliate.Â